The effect of landfill leachate treatment on ecotoxicological properties of Folsomia candida, with a focus on soil contamination risks - Dorota Szydełko; Aleksandra Wdowczyk; Iwona Gruss (Scientific Reports)
Abstract Landfilling is a common method for managing solid waste, but it generates leachate, a highly contaminated liquid that can threaten groundwater, surface water, and soil health. This study examines how raw and treated landfill leachate affects the survival and reproduction of Folsomia candida, a soil-dwelling Collembola species. Leachate treatment was conducted using Vegetation-activated sludge process with different fill materials (zeolite, biochar) and plant variations. The study also explored the relationship between leachate toxicity and its chemical properties to determine key contaminants influencing F. candida. The results showed that both raw and treated leachate reduced Collembola reproduction, with most treatments exhibiting toxicity levels similar to untreated leachate. The number of juveniles decreased by 49.8% with the biochar–plant system and by 64.9% with biochar. The number of adults decreased by 24.4% from day 7 to day 42. Redundancy analysis (RDA) revealed that iron (Fe) was strongly associated with increased mortality, while total dissolved solids (TDS) and organic nitrogen (ON) were positively linked to juvenile abundance. Although the treatment systems removed some contaminants, they were not fully effective, leaving residual pollutants that could pose environmental risks. These findings highlight the need for improved treatment methods to minimize leachate toxicity and protect soil ecosystems.